Fermentation conditions for mannitol biosynthesis by lactobacillus fermentum hf08 - Hưng, Đỗ Trọng; Mạnh, Lê Đức; Anh, Nguyễn La; Thuận, Vũ Thị; Linh, Nguyễn Thuỳ; Như Hoa, Lương Thị; Phi, Nguyễn Hoàng (Vietnam Journal of Biotechnology, 2018)
Mannitol is a six-carbon sugar alcohol that is claimed to have several health promoting effects (low-caloric, low-glycemic, low-insulinemic, anticariogenic, and prebiotic). Due to its low hygroscopic character, it widely used in food and pharmaceutical industries. In food industry, mannitol is used as sugar replacers because of their taste and sweetness. It is nonmetabolizable sweeteners which do not affect insulin levels making it applicable in diabetic food products. Among mannitol production methods including: chemical, enzyme and fermentation, the conversion of fructose to mannitol by lactic acid bacteria fermentation is the best way because of no requirement for highly purified substrates, making pure product and easy to produce in industry scale. There are many groups of microorganisms capable of fermenting mannitol biosynthesis, including lactic acid bacteria group, because of their conversion of fructose to mannitol by mannitol dehydrogenase with high mannitol content and low byproducts. In the study, we researched on conditions of fermentation for mannitol biosynthesis by Lactobacillus fermentum HF08. Mannitol production of the strain was reached to the maximum 93.1-93.2 g/l after 48 hours of fermentation in an appropriate medium (g/l): pepton 7.0; glucose/fructose 50/100; yeast extract 2.0; K2HPO4 2.0; MgSO4.5H2O 0.2; MnSO4 0.01. The pH of the medium fermentation for the mannitol production was 5.0-5.5. Suitable temperature for mannitol production was 35-37oC.